PENGARUH PENGALAMAN AUDITOR, LOCUS OF CONTROL DAN REPUTASI AUDITOR TERHADAP KUALITAS AUDIT DENGAN PEMAHAMAN SISTEM INFORMASI SEBAGAI VARIABEL MODERASI - Nadia Sri Damayanti (2022)
This study is a quantitative study that aims to determine the effect of experience, locus of control, reputation on audit quality with an understanding of information systems as moderation. The population of this research are auditors who work in KAP in Central Jakarta and South Jakarta. The sample consisted of 70 respondents and was selected by purposive sampling method. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS version 3.0 software. The results obtained in the study can be ascertained that experience has an effect on audit quality, while locus of control and reputation have no effect on audit quality. Understanding of information systems does not moderate the effect of experience, locus of control, reputation on audit quality.